Green preference, green investment - Zhenyu Gao; Yan Luo; Shu Tian; Hao Yang (Asian Development Bank (ADB), 2024)
Based on Alibaba's renowned "green" initiative, the Ant Forest program, we develop a novel measure to reveal an individual investor's nonpecuniary green preference and link it to an individual's investment actions. We present compelling evidence that supports nonfinancial incentives for investing in green mutual funds while divesting from "brown" funds. Concerns over climate physical and regulatory risks further reinforce this influence. Individuals' green preferences do not lead to financial gains from trading. Moreover, we mitigate the endogeneity issue by employing the development of a local subway network as a source of variations in green preferences.
Keywords: G11; G50; Q55; 330; nonpecuniary preference; revealed preference; sustainable finance; FinTech